PENERAPAN METODE DRILL DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SANTRI DI TPA AR-ROMLY TANJUNGSARI JOGOROGO - Farihah, Elyaum; Sanusi, Gucik (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
Ar-Romly Tanjungsari, Jogorog, Ngawi TPA, located in Tanjungsari Village, Jogorogo, Ngawi, was established from the start to produce Muslim cadres who are able to read fluently and correctly. Along with the rapid development of the times, the Al-Qur'an Education Park in the Tanjungsari area really needs guidance and teaching, especially in the field of reading according to recitation. Al-Qur'an education in the Siman area consists of students who are still in iqra', the Qur'an. However, it is very unfortunate, the development of non- formal education, students still do not understand about learning recitation. This is because the ustadz and ustadzah are still lacking in adding recitation material, the educators there only teach reading the Qur'an correctly but the level of fluency and knowledge of recitation is still lacking. After doing a method that I apply, namely the drill method where students will be given recitation material and practice fluent Arabic letters with chanting songs so that they are easy to memorize. And there is a moment where the santri are appointed one by one to indicate which one of the verses of the Qur'an is included in the law of recitation. Targets with such plans and procedures can add additional knowledge and insight for the students. They are so excited when they receive a new learning, namely recitation, but there are still those who feel confused and need guidance that is easily understood by the students